Human resource management and the performance of selected small and medium manufacturing enterprises - Mohd Rosli Mohamad (2011)
Despite many studies on human resource management can be found in the literature, until recently, studies on the moderating effects of this factor on innovation and firm performance are hardly exixtent. In filling the literature gap, this study attempts to address the questions of how HRM practices and its interactions with innovation affect the performance of SMEs. Two hundred eighty-four samples were obtained from the food and beverage, textile and clothing and wood-based small and medium manufacturing enterprises in Malaysia. Using the multiple regression analysis, this study found that human resource management practices in terms of employee and employer's training interacted with innovation and significantly affected the performance of SME's